MICROENCAPSULATION OF Cytrus hystrix OIL AND ITS ACTIVITY TEST AS AN ANTIMICROBIAL AGENT - Warsito Warsito; Noorhamdani Noorhamdani; Sukardi Sukardi; Rissa Dwi Susanti (Journal of Environmental Engineering and Sustainable Technology, 2017)
Microencapsulation Kaffir lime oil (C. hystrix DC.) has advantages such as capable of controlling the evaporation process, oxidation by air or oxygen and release the active ingredient is stable, thus providing a constant concentration over long periods of therapy. In this research microencapsulation of kaffir lime oil from leaves (MJP-D) and rind (MJP-KB) using chitosan to crosslinking with glutaraldehyde (ratio 2:1). Characterization of kaffir lime oil use Gas chromatography-mass spectrometry (GC-MS), characterization of microcapsule use FTIR and particle size analyzer, while analysis of essential oil content in the microcapsules with UV-Vis spectroscopy. Composition of MJP-D consist of citronellal (85,07%), lonalool (3,47%), citronelil acetate (2,77%) and sabinene (2,79%), while MJP-KB consist of citronellal (20,91%), terpinen-4-ol (11,93%), a-pinene (21,44%) and limonene (12,59%). Microcapsul MJP-D and MJP-KB has a distinctive absorption crosslinking results on 1558 cm-1 (-C=N) and particle size 340,43-404,90 nm. The effectiveness microcapsulation of MJP-D and MJP-KB 37,5% and 86,88% with each zone of inhibition against Pseudomonas aeruginosa bacteria is 12,8 mm and 17,1 mm. Keywords: microcapsul, kaffir lime oil, antimicrobial P. aeruginosa